Development of a problem-based learning interactive quiz for fifth-grade mathematics - Win Siti Suciati; Abna Hidayati; Jasrial Jasrial; Hani Fannisa (Global Econedu, 2026)
This study aimed to develop and evaluate the validity and practicality of a Problem Based Learning (PBL)-based interactive quiz for teaching fractions and decimals in elementary school mathematics. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observations, interviews, expert validation sheets, and practicality questionnaires. The product was validated by media and material experts, while practicality was assessed through teacher responses. The needs analysis indicated that students experienced difficulties in understanding fractions and decimals and required more interactive learning media. The developed product was a web-based interactive quiz integrating contextual problem-solving activities. Media validation obtained a mean score of 3.14 (valid), material validation achieved 3.73 (very valid), and teacher practicality reached 3.86 (very good). The developed PBL-based interactive quiz is valid and practical for supporting mathematics learning on fractions and decimals at the elementary school level.